The contribution of periaqueductal gray in the regulation of physiological and pathological behaviors - Zhang, Hui; Zhu, Zhe; Ma, Wei-Xiang; Kong, Ling-Xi; Yuan, Ping-Chuan; Bu, Li-Fang; Han, Jun; Huang, Zhi-Li; Wang, Yi-Qun (Frontiers in Neuroscience, 2024)
Periaqueductal gray (PAG), an integration center for neuronal signals, is located in the midbrain and regulates multiple physiological and pathological behaviors, including pain, defensive and aggressive behaviors, anxiety and depression, cardiovascular response, respiration, and sleep-wake behaviors. Due to the different neuroanatomical connections and functional characteristics of the four functional columns of PAG, different subregions of PAG synergistically regulate various instinctual behaviors. In the current review, we summarized the role and possible neurobiological mechanism of different subregions of PAG in the regulation of pain, defensive and aggressive behaviors, anxiety, and depression from the perspective of the up-down neuronal circuits of PAG. Furthermore, we proposed the potential clinical applications of PAG. Knowledge of these aspects will give us a better understanding of the key role of PAG in physiological and pathological behaviors and provide directions for future clinical treatments.